Geometric design of a masonry lattice space dome titled KARBANDI in Persian architecture. Issue 1 (March 2019) - Amjad Mohammadi, Amir; Nejad Ebrahimi, Ahad; Shahbazi, Yaser
Studies of historical buildings in Persian architecture have resulted in knowing a kind of masonry structure with a harmonic lattice geometry, which has been titled "Karbandi." The most important and highly acclaimed feature of Karbandi is the correlation and coordination between its architectural and structural functions, which results in creating esthetic and meaningful spaces. The use of this structure is highly demanded in contemporary Persian architecture, but very little information about historical techniques survives to the present day and accordingly, there are ambiguities about its drawing and geometric design. Therefore, this research aims at discovering geometric relationships and principles of Karbandi to regulate and facilitate its design process in contemporary architecture. Toward this end, its historical samples were analyzed and their geometric features were found. As a consequence, the connection distance of dividing points on the circle is an important parameter for creating various types of Karbandi on a base. For instance, the height of a Karbandi and its elaboration are directly related to the connection distance. In addition, it was clarified that the height of a Karbandi and the size of its Shamseh are in an inverse relationship. Finally, a comprehensive classification was presented based on found geometric features.